Improved electrical and photosensing properties of CuPc phtalocyanine/p-silicon diode by nanostructure - Cavas, M.; Aydin, M. Enver; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2012)
The electrical and photovoltaic properties of metal/nanostructure CuPc phtalocynine organic layer /semiconductor diode have been investigated. The diode indicated a good rectifying behavior with non-linear behavior due to the organic and inorganic interfacial layers. The barrier height (0.77 eV) and ideality factor (1.99) of the studied diode is higher than that of conventional Al/p-Si Schottky diode. This indicates that barrier height could be increased by using CuPc phtalocynine organic layer on p-type silicon by changing the space charge region of p-type silicon. The photovoltaic parameters of the diode were found to be Voc=0.25 and J(sc)=607.2 mu A under AM1.5. The obtained results indicate that the barrier height of conventional Al/p-Si Schottky diode can be increased by organic modification and metal/nanostructure CuPc/semiconductor diode can be used for optoelectronic device applications as a photosensor.
Keywords: Organic-inorganic diodes; Photosensor; CuPc phtalocynine